Design for manufacture using machining features on CNC machining centers - Festa, Pedro Manuel de Oliveira (2021)
Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) systems have become more and more needed and useful in the machining processes environment. In order to achieve competitive advantage, companies adopted new manufacturing methods. As a consequence, and in machining processes context, the interaction of CAD and CAM has growth over the years in order to increase the production efficiency, as well as to reduce costs and time. The development of this work started with an extensive literature review. In that review, the author found that only a few articles approached the interaction or integration of CAD and CAM systems. Moreover, the authors that studied this interaction focused on systems for turning parts. Thus, there is a gap in the literature related to the integration and automation of these systems when applied to milling parts. Therefore, the purpose of this dissertation is to enable the interaction of these systems in order to provide a completely automated process since the design stage until the machining stage. Finally, the process’ implementation showed that the developed algorithm was able to satisfy the initial requirements of this work, i.e., when given a set of initial parameters, the program drew the required geometry, and then generated the required G-code, such that this code can be sent to the CAM software to machine the workpiece, thereby obtaining the final product.